2003
DOI: 10.1002/anie.200351128
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Rotaxane Constructed from the Inclusion Complex of β‐Cyclodextrin and 4,4′‐Dipyridine by Coordination with Nickel(II) Ions

Abstract: The missing link: NiII ions have been used to coordinate to 4,4′‐dipyridine included within β‐cyclodextrin to form a linear polymeric rotaxane (see schematic representation). The binding of the 4,4′‐dipyridine within the cyclodextrin has been examined both in solution and in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
51
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(56 citation statements)
references
References 33 publications
5
51
0
Order By: Relevance
“…The results of their further study on the size effect of the homologues of the a,x-diphenylpolyenes series, with two, three, and four double bonds, on the formation of nanotubes with c-CD indicated that the length of guest molecule is a key factor in the course of nanotube formation [5]. Liu et al focused on the artificial design of CD nanotubes induced by different CD derivatives and metal ions through the metal-ligand coordination [6][7][8].…”
Section: Introductionmentioning
confidence: 97%
“…The results of their further study on the size effect of the homologues of the a,x-diphenylpolyenes series, with two, three, and four double bonds, on the formation of nanotubes with c-CD indicated that the length of guest molecule is a key factor in the course of nanotube formation [5]. Liu et al focused on the artificial design of CD nanotubes induced by different CD derivatives and metal ions through the metal-ligand coordination [6][7][8].…”
Section: Introductionmentioning
confidence: 97%
“…Some of the most common hosts are the cyclodextrins (CDs), which are cyclic oligosaccharides with hydrophobic cavities that can house nonpolar guests. They often lead to the formation of one-dimensional supramolecular inclusion polymers456789, typically pseudopolyrotaxanes, with a wide variety of organic101112, organometallic13141516171819 and inorganic20212223 guests. The structural compatibility between the CDs and the guests is the key preorganization parameter to consider when designing CD inclusion complexes, while hydrophobic interactions24, in addition to second-sphere coordination252627, provide major contributions to the stabilities of these complexes.…”
mentioning
confidence: 99%
“…The majority of inclusion compounds with metal complexes known to date exhibit an organometallic complex (i.e., metallocenes, olefin metal complexes, metal alkyls, and carbonyls) encapsulated inside the cavity of a macrocyclic host. Their molecular frameworks are constructed by strong interactions, such as covalent and coordination bonds [3][4][5][6], making them usable as coordination complexes and valuable to research. One significant use of such complexes is to employ them as single source precursors to prepare nano-structured or micro-structured materials.…”
Section: Introductionmentioning
confidence: 99%